THE APPLICATION OF Fe AND Cr(III) IN GROWING MEDIA AND ITS EFFECT ON PLANT GROWTH AND Cr(III) OXIDATION ON Tagetes erecta - Kasmiyati, Sri (BRIN - Badan Riset dan Inovasi Nasional, 2022)
The oxidation of Cr(III) to Cr(VI) in the environment has a detrimental impact because it can change the form of non-toxic Cr(III) to Cr(VI), which is toxic to organisms. The study aimed to examine the effect of the application of iron (Fe) and trivalent chromium (Cr(III)) compounds in Tagetes erecta growing media on growth and Cr(III) oxidation. Concentrations of Cr(III) 0, 100, and 500 mg/L and Fe 0, 3, 15, and 30 mg/L were applied to the growing media of T. erecta as the model plant. The growth and accumulation of Cr(VI) in plants were measured to determine the effect of Fe and Cr(III) treatment on growth and Cr(III) oxidation. The accumulation of Cr(VI) in the roots and shoots of T. erecta increased significantly due to the addition of Fe in the growing media treated with Cr(III). The highest accumulation of Cr(VI) in the roots and shoots of T. erecta found in the treatment of Cr(III) 500 mg/L and Fe 30 mg/L, were respectively 0.092 g/L and 0.070 g/L. The addition of Fe in growing media containing Cr(III) increased plant height, root length, and shoot dry weight but decreased leaf number and root dry weight. T. erecta root biomass was more affected by the toxic impact of Fe than Cr(III). On the other hand, the inhibition of leaf formation was caused by the toxic effect of Cr(III) rather than Fe.